Programming : logistic and design introductory - Farell, Joyce (Andover : Cengage Learning Asia Pte Ltd, 2016)
"PROGRAMMING LOGIC AND DESIGN, INTRODUCTORY, 8E. This popular introductory book takes a unique, language-independent approach to programming with a clear, concise approach that eliminates highly technical jargon while emphasizing universal programming concepts and encouraging a strong programming style and logical thinking. Clear revised explanations utilize flowcharts, pseudocode, and diagrams to ensure even readers with no prior programming experience fully understand modern programming and design concepts. Farrell's proven learning features help students gain a better understanding of the scope of programming today while common business examples help illustrate key points. Readers can use this proven book alone or paired with a language-specific companion text that emphasizes C++, Java or Visual Basic. Programming Logic and Design, Introductory combines text explanation with flowcharts and pseudocode examples to provide students with alternative means of expressing structured logic. Numerous detailed, full-program exercises at the end of each chapter illustrate the concepts explained within the chapter, and reinforce understanding and retention of the material presented."
Includes bibliographical references.
English text.
Keywords: Logic programming; Logic design; Computer programming